THU0563 Ultrasound changes in joints induced by intra-articular corticosteroid injection in juvenile idiopathic arthritis. (12th June 2018) - Sozeri, B.; Bolac, L.G.; Kariminikoo, M.
Abstract : Background: Ultrasonography (US) studies carried out on joints of juvenile idiopathic arthritis (JIA) patients in clinical remission demonstrate the presence of subclinical synovitis. The significance of subclinical synovitis and the positive power Doppler (PD) signal on US in JIA. Objectives: The objectives of this study were to assess whether the changes detected by US induced by intra-articular corticosteroid injection in JIA patients. Methods: We evaluated 49 joints (47 knees, 1 tibiotalar and 1 elbow) of 32 patients who diagnosed JIA. We used grey-scale US by high frequency transducer (7.5–10) MHz at study entry and after a therapeutic intervention. Each joint was scored for grey-scale (GS) and power Doppler (PD) abnormalities according to a 4-point semiquantitative scale. Pre- and post-treatment US scores were compared and the sensitivity to change of GSUS and PDUS was estimated. US assessment was performed separately, immediately after the clinical evaluation, by an experienced paediatric rheumatologist (BS) with certificated by EULAR. Medical records were reviewed for JIA subtype and state of disease. Clinical examination, including routine joint examination was carried. Clinical response was assessed using the ACR paediatric (pedi ACR) response criteria Results: Five patients had polyarthritis, 5 had enthesitis-related arthritis, 22 had oligoarthritis. Nine patients (28%) underwent intra-articular corticosteroid injection (IACI) only, 23 (71, 9%) were given IACI and systemic medications. The medication used were methotrexate (22 patients), Sulfasalazine (2 patients), and methotrexate and biologic (5 patient). Synovial hyperplasia, joint effusion, PD signal and tenosynovitis in at least one joint were detected in 77.4%, 100%, 33.3% and 15% of patients, respectively. Both GSUS and PDUS scores improved significantly (p<0.0001) from baseline to follow-up. At the follow-up visit, 18/49 (36.7%) joints complete resolution among these patients 2 had minimal synovial hyperplasia. Although, 31/49 (63.3%) joints residual US abnormalities were judged in remission on clinical grounds. Conclusions: US is a sensitive tool to assess therapeutic response in patients with JIA. Subclinical disease on US is common in joints with clinically-defined remission.. Further studies are needed to establish the impact of US on therapeutic decision-making in JIA. Disclosure of Interest: None declared